The age in swimming of champions in World Championships (1994-2013) and Olympic Games (1992-2012): A cross-sectional data analysis - Knechtle, B.; Bragazzi, N. L.; König, S.; Nikolaidis, P. T.; Wild, S.; Rosemann, T.; Rüst, C. A. (Sports, 2016)
(1) Background: We investigated the age of swimming champions in all strokes and race distances in World Championships (1994-2013) and Olympic Games (1992-2012); (2) Methods: Changes in age and swimming performance across calendar years for 412 Olympic and world champions were analysed using linear, non-linear, multi-level regression analyses and MultiLayer Perceptron (MLP); (3) Results: The age of peak swimming performance remained stable in most of all race distances for world champions and in all race distances for Olympic champions. Longer (i.e., 200 m and more) race distances were completed by younger (-20 years old for women and -22 years old for men) champions than shorter (i.e., 50 m and 100 m) race distances (-22 years old for women and -24 years old for men). There was a sex difference in the age of champions of -2 years with a mean age of -21 and -23 years for women and men, respectively. Swimming performance improved in most race distances for world and Olympic champions with a larger trend of increase in Olympic champions; (4) Conclusion: Swimmers at younger ages (<20 years) may benefit from training and competing in longer race distances (i.e., 200 m and longer) before they change to shorter distances (i.e., 50 m and 100 m) when they become older (>22 years).